MAKNA SIMBOL DALAM KEBUDAYAAN MANUSIA - A., Agustianto (Jurnal Ilmu Budaya, 2011)
Humans are cultural creatures and culture is full of symbols. Thus humans’ culture is identified with symbol. It is an aim or a thought which stresses on patterns relying on symbols. Along the history of human culture, symbols determine humans’ behavior, science, knowledge and religion.